Targeting visual-sensory and cognitive impairments following lateral ankle sprains: a practical framework for functional assessment across the return-to-sport continuum. Part 2: from theory to practice: recommendations for optimizing return to sport after lateral ankle sprains using cognitive and visual-sensory assessments - Picot, Brice; Maricot, Alexandre; Fourchet, François; Gokeler, Alli; Tassignon, Bruno; Lopes, Ronny; Hardy, Alexandre (Frontiers in Sports and Active Living, 2025)
Lateral ankle sprain (LAS) is the most common traumatic injury in sports, characterized by a high recurrence rate, with chronic ankle instability (CAI) developing in ∼40% of cases. Both altered sensory reweighting and cognitive impairments have been identified as potential contributors to the elevated risk of (re)injury. The first part of this work aimed to clarify cognitive constructs relevant to post-injury rehabilitation, alongside the concept of sensory reweighting that may be observed in patients following LAS. It also introduced the Ankle-GO™, the first validated score providing clinicians with an objective criterion to support return-to-sport (RTS) decision-making. However, this promising tool does not account for visual and cognitive constraints encountered during functional tasks. Therefore, the second part of this work aims to translate emerging theories and growing evidence into practical applications, illustrating concrete examples of RTS assessments in patients with LAS and CAI. This perspective's article proposes a “β(rain)” extension of the Ankle-GO™ integrating dual-tasks paradigms and visual constraints to better approximate sport-specific conditions. Each functional test (Single leg stance, modified Star Excursion Balance Test, Side Hop Test and Figure-of-8 test) is paired with either a dual-tasks targeting key cognitive domains or a visual constraint. An adapted scoring method is outlined, together with a guide for interpreting results during the late rehabilitation phase, tailored to patients' specific deficits.